One-Pot Sonochemical Synthesis of ZnO Nanoparticles for Photocatalytic Applications, Modelling and Optimization - Noman, Muhammad Tayyab (Materials (Basel), 2019)
This present study proposed a successful one pot synthesis of zinc oxide nanoparticles (ZnO NPs) and their optimisation for photocatalytic applications. Zinc chloride (ZnCl(2)) and sodium hydroxide (NaOH) were selected as chemical reagents for the proposed study. The design of this experiment was based on the reagents’ amounts and the ultrasonic irradiations’ time. The results regarding scanning electron microscopy (SEM), X-ray diffraction (XRD) and Raman spectroscopy confirmed the presence of ZnO NPs with pure hexagonal wurtzite crystalline structure in all synthesised samples. Photocatalytic activity of the developed samples was evaluated against methylene blue dye solution. The rapid removal of methylene blue dye indicated the higher photocatalytic activity of the developed samples than untreated samples. Moreover, central composite design was utilised for statistical analysis regarding the obtained results. A mathematical model for the optimisation of input conditions was designed to predict the results at any given point. The role of crystallisation on the photocatalytic performance of developed samples was discussed in detail in this novel study.